2017
DOI: 10.1021/acs.chemrev.6b00833
|View full text |Cite
|
Sign up to set email alerts
|

Methods Utilizing First-Row Transition Metals in Natural Product Total Synthesis

Abstract: First-row transition-metal-mediated reactions constitute an important and growing area of research due to the low cost, low toxicity, and exceptional synthetic versatility of these metals. Currently, there is considerable effort to replace existing precious-metal-catalyzed reactions with first-row analogs. More importantly, there are a plethora of unique transformations mediated by first-row metals, which have no classical second- or third-row counterpart. Herein, the application of first-row metal-mediated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(74 citation statements)
references
References 856 publications
(1,060 reference statements)
0
67
0
Order By: Relevance
“…9,10 More importantly, copper shows excellent reactivity: Cu 0 , Cu I , Cu II , and Cu III oxidation states can be easily accessed, enabling radical pathways or two-electron bond formations. In addition to its redox properties, copper has the additional possibility of acting as a Lewis acid either through σ coordination to basic oxygen functionality or through π coordination with numerous functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 More importantly, copper shows excellent reactivity: Cu 0 , Cu I , Cu II , and Cu III oxidation states can be easily accessed, enabling radical pathways or two-electron bond formations. In addition to its redox properties, copper has the additional possibility of acting as a Lewis acid either through σ coordination to basic oxygen functionality or through π coordination with numerous functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with noble transition metals (Pd, Ru, Rh, Ir, Pt), non‐noble transition metals, such as Fe, Co, and Ni, are attracting increasing attention in C−H activation because they are relatively earth‐abundant and less toxic . Notably, a perspective article on electrochemical cobalt‐catalyzed C−H bond activation has been published recently …”
Section: Anodic Cobalt‐catalyzed C−h Bond Functionalizationmentioning
confidence: 99%
“…The insertion reactions of activated alkynes into the metal–hydride bond of metallocene hydride, especially the compounds containing Nb and Ta of group 5, continuously attract much attention, while studies on vananocenehydride have rarely been reported. In fact, the first‐row transition‐metal‐mediated reactions constitute an important and growing area of research owing to the low cost, low toxicity and exceptional synthetic versatility of these metals . The unique properties of first‐row transition metals, especially their generally reduced electronegativity, offer orthogonal opportunities for reaction development relative to their second‐ and third‐row counterparts.…”
Section: Introductionmentioning
confidence: 99%